Analysis of the Influence of Hard Skill Competencies, Training and Application of Information Technology on the Performance of One Stop Integrated Service Investment Service Employees in Aru Islands Regency - Selly, Rino; Risambessy, Agusthina; Leuhery, Ferdy (Jurnal Ekonomi, 2024)
This research aims to determine whether there is an influence of hard skills competency, training and the application of information technology on the performance of employees of the investment service and one-stop integrated services in the Aru Islands district. The data collection method is by distributing questsionnaires to employees at the one-stop investment and integrated services service (DPMPTSP) of the Aru Islands district. The population of this study was 30 employees, while the sample used a saturated sample, where the entire population was used as the research sample, namely 30 employees. The analytical method used is multiple linear regression analysis using IBM SPSS 29. The research results which were tested partially show that hard skill competency has a positive and significant effect on employee performance, training has a positive and significant effect on employee performance, the application of information technology has a positive and significant effect on the performance of employees of the investment department and one-stop integrated services in the Aru Islands district.